Rapid Determination of Metronidazole and 2-Hydroxymetronidazole in Murine Blood Plasma - Zemanová, Nina; Anzenbacher, Pavel; Hudcovic, Tomáš; Anzenbacherová, Eva (Journal of chromatographic science, 2022)
Metronidazole is a drug used to treat bacterial and protozoan infections. Nowadays, it is one of the most frequently prescribed drugs worldwide. The main aim of this paper is to present a rapid, reliable and simple high-performance liquid chromatography (HPLC) method to determine metronidazole along with its primary metabolite, 2-hydroxymetronidazole, in plasma or serum using paracetamol as an internal standard. A total of 100% methanol was used to denature plasma proteins. After centrifugation, the supernatant was evaporated under nitrogen flow. The samples were dissolved in the mobile phase and injected into a Li-Chrospher RP-18 column. A total of 10 mmol/L NaH2PO4: acetonitrile (90:10, v/v) solution with a flow rate of 1 mL/min was used as the mobile phase. Metronidazole and 2-hydroxymetronidazole were detected at two different wavelengths at 320 nm and 311 nm, respectively. The method is characterized by high precision (relative standard deviation % < 6). The method was used for the determination of metronidazole and 2-hydroxymetronidazole in murine blood using small amounts of plasma (≤100 μL).
Keywords: Metronidazole; Chromatography, High Pressure Liquid; myši; krevní plazma; Animals; Mice; Plasma; metronidazol; zvířata; vysokoúčinná kapalinová chromatografie